2016
DOI: 10.1371/journal.pone.0165727
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical and Biochemical Predictors of Bone Mass in Preterm Infants

Abstract: BackgroundMetabolic bone disease of prematurity still occurs in preterm infants, although a significant improvement in neonatal care has been observed in recent decades. Dual-energy X-ray absorptiometry (DXA) is the precise technique for assessing bone mineral content (BMC) in preterm infants, but is not widely available.AimTo investigate the clinical and biochemical parameters, including bone metabolism markers as potential predictors of BMC, in preterm infants up to 3 months corrected age (CA).Materials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 50 publications
0
24
0
4
Order By: Relevance
“…Czech‐Kowalska et al . reported that PTH was the only independent predictor of low bone mass in ex‐preterm infants who had DEXA at 40 weeks corrected gestational age …”
Section: What Is Already Known On This Topicmentioning
confidence: 99%
“…Czech‐Kowalska et al . reported that PTH was the only independent predictor of low bone mass in ex‐preterm infants who had DEXA at 40 weeks corrected gestational age …”
Section: What Is Already Known On This Topicmentioning
confidence: 99%
“…However, despite its specificity, there is no a clear relationship between serum OC levels and bone mineral content in the first 4 months of life (33). It has been demonstrated that serum PTH levels might predict a reduction of bone mineral content in preterm infants who have reached the at term age, while urinary phosphate excretion and OC might be useful markers to predict a low bone mineralization at 3 months of corrected age (34).…”
Section: Introductionmentioning
confidence: 99%
“…When combined with low serum phosphate, an elevated PTH was 100% sensitive and 94% specific in identifying MBDP. In 160 preterm infants, Czech-Kowalska et al 56 found only PTH to be a predictor of low bone mineral content at term age using DXA scan. Considering the pathophysiology, one would expect that plasma PTH would become elevated earlier than changes in ALP or phosphate.…”
Section: Introductionmentioning
confidence: 99%